Evaluation of occupational safety and health management system in a hospital related to infection prevention and control program: hand hygiene - Maria Saraswati Kinasih Hapsari; Anggit Wirama Siwidati; Ratna Hafitri Astutik; Asri Deismawaranti (Berita Kedokteran Masyarakat, 2026)
Purpose: This study evaluates the implementation of the Occupational Safety and Health Management System (OSHMS) through a hand hygiene program at Griya Mahardhika General Hospital, focusing on five elements: policy establishment, planning, implementation, monitoring, and perform- ance improvement. Methods: This study employed a descriptive qualitative approach involving the Infection Prevention and Control (IPC) team and hospital management, with documents, facilities, and procedures related to hand hygiene implementation as the research objects. Data were collected through in-depth interviews with five key informants, direct observations, and document reviews based on hospital regulations and Ministry of Health standards. Results: Griya Mahardhika General Hospital has implemented internal policies aligned with Ministry of Health Regulation No. 27 of 2017 through a Director’s Decree and established an IPC Team with a clear organizational structure. Implementation efforts include sanitation facilities, educational posters, routine training, and collaboration with professional infection control associations. Monitoring of hand hygiene compliance using the “6 steps” and “5 moments” checklists is reported internally and through the mutu fasyankes platform, with support from the local health office. However, compliance varies across departments, and monitoring is conducted only occasionally due to staffing limitations. Conclusion: The hand hygiene program at Griya Mahardhika General Hospital has been implemented in accordance with the five elements of the Occupational Safety and Health Management System. Structured implementation, internal monitoring, and external supervision are crucial for preventing infections. Strengthening staff awareness and maintaining cross-sector collaboration are key to sustaining the Occupational Safety and Health Management System (OSHMS) in hospital settings.